The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s43076-021-00116-9
|View full text |Cite
|
Sign up to set email alerts
|

The Global Prevalence of Depression, Anxiety, Stress, and Insomnia Among General Population During COVID-19 Pandemic: A Systematic Review and Meta-analysis

Abstract: This study aimed to examine research findings related to depression, anxiety, stress, and insomnia during the COVID-19 pandemic. This study also explored periodic changes in the prevalence of depression, anxiety, stress, and insomnia among the general people during this pandemic. We performed a meta-analysis by searching articles from several sources (PubMed, MEDLINE, and Google Scholar). We used the random-effects models, subgroup analysis, and heterogeneity test approaches. Results show that the prevalence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 84 publications
4
47
1
2
Order By: Relevance
“…For example, a global review from the early stages of the pandemic found that the prevalence of depression, anxiety, and distress symptoms worldwide were 28.18%, 29.57%, and 25.18%, respectively. In contrast, another review of data from the first year of the pandemic suggested that the prevalence of depression, anxiety, and distress was 31.4%, 31.9%, and 41.1%, respectively, indicating sharp increases [ 8 , 9 ]. Several reviews also focused on special populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a global review from the early stages of the pandemic found that the prevalence of depression, anxiety, and distress symptoms worldwide were 28.18%, 29.57%, and 25.18%, respectively. In contrast, another review of data from the first year of the pandemic suggested that the prevalence of depression, anxiety, and distress was 31.4%, 31.9%, and 41.1%, respectively, indicating sharp increases [ 8 , 9 ]. Several reviews also focused on special populations.…”
Section: Introductionmentioning
confidence: 99%
“…This also translates into an estimated productivity loss of €6,013 per person, with an estimated total productivity loss of 200 million euros per year as a result of work days lost due to temporary disability caused by depression (Salvador-Carulla et al, 2011). These outcomes highlight the urgent need to find new ways of applying cost-effective psychological evidence-based treatments in the SPMH to cover the great demands of society in relation to mental health care and will also lead to an improvement in factors related to work performance (Ihara et al, 2021;Mahmud et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These six items gave rise to a new, shorter version of the CIS (CIS-6). The presence of these six items in this new version is to be expected since symptoms of depression and stress are among the most characteristic during the pandemic worldwide, with a prevalence of 28.18% and 25.18% respectively [55]. In Peru, between 18.1% and 39% of people have presented symptoms of depression; while 15% stress symptoms [56,57].…”
Section: Discussionmentioning
confidence: 99%